Vaginal repair of vaginal vault dehiscence after postpartum hysterectomy - Avcıoğlu, Sümeyra Nergiz (Oxford University Press, 2014)
Vaginal vault dehiscence (VVD) may occur rarely after hysterectomy. Although mostly, a vaginal cuff dehiscence is seen after robotic or laparoscopic hysterectomy, it may also be observed as a complication of abdominal or vaginal hysterectomy. Vaginal repair is one of the techniques used for VVD. Here, we will describe a case of vaginally repaired VVD, associated with intra-abdominal hematoma after postpartum hysterectomy.